Copolar Synchronous Switching Method for BLDC Motor Control in EV Application - Yueh-Tsung Shieh; Gang-Ting Liou; Shyr-Long Jeng; Wei-Hua Chieng; Jih-Sheng Lai; Edward-Yi Chang (IEEE Access, 2025)
This paper proposes a new PWM switching method, called copolar switching, for synchronous rectification in brushless DC motors (BLDC). This method-integrates the benefits of both unipolar and bipolar switching, addressing the efficiency trade-off commonly observed in low-resistance BLDC drives. Unipolar switching is known to reduce current ripple and switching losses at low speeds, while bipolar switching enhances efficiency during high-speed operation due to faster recovery of freewheeling current. However, most existing methods statically adopt one scheme, leading to suboptimal performance across variable-speed conditions. The proposed copolar switching method combines unipolar switching at zero-speed for ripple-free conduction, and switches to bipolar mode at higher speeds to enable rapid energy feedback to the source. Therefore, it can be used in electric vehicles (EV) applications to increase the average power efficiency. The EV simulation in this paper identified there could be a 5% efficiency improvement.